Fatal case of classic Potter’s syndrome: a case report - Agarwal, Deepika; Mazahir, Rufaida; Singh, Rupa (International Journal of Contemporary Pediatrics, 2022)
Potter’s syndrome is a rare complication of oligohydramnios, incidence varies from 1 in every 2,000 to 5,000 fetuses with an average of 1 in 4,000. It is reported in 0.2-0.4% of autopsies in dead new-born who die immediately after birth. Potter’s syndrome primarily affects male fetuses (2:1) and is characterized by pulmonary hypoplasia and renal failure. Here, we are presented a case of classic Potter’s syndrome with fatal outcome. The baby was a live preterm male, born to a 28 years old multigravida, out of a non-consanguineous marriage via caesarean section. There was absolutely no liquor at the time of delivery. The baby did not cry immediately after birth and required resuscitation followed by mechanical ventilation. Multiple congenital anomalies suggestive of Potter’s syndrome were noted including facial features such as low set ears with overturned helix, slanting eyes, redundant fold of skin beneath the cheeks, prominent epicanthal fold, receding chin, flattened broad ear, flat nasal bridge, parrot beak appearance of nose and triangular facies. Chest X-ray showed small volume lung fields suggestive of pulmonary hypoplasia, and both kidneys were absent on ultrasonography indicating bilateral renal agenesis. At 15 min of life, baby developed tachypnea and severe chest retractions and succumbed after 1 hour of birth due to respiratory insufficiency. This case report emphasizes upon the importance of regular antenatal check-ups in every patient as it picks up the suspicious cases, leading to further workup and diagnosis, resulting in a timely decision regarding management.